Társadalmi programunk a fejlett szocializmus . Our social program is developed socialism - írta: dr. Zentai Artúr. (Magyar Diafilmgyártó Vállalat, 1975)
Produced for the Hungarian People's Army Financial and Methodological Centre for Political Education.